Conflict of securities : reflections on state and human security in Africa - Omeje Kenneth; Galadima Habu (London; Adonis & Abbey Publishers Ltd, 2010)
include index
Keywords: Conflict management-Nigeria; Human security-Nigeria; National security-Nigeria; Peace building- Nigeria; Ethnic conflict-Nigeria